Financing education in India : current issues and changing perspectives - National Seminar on Financing of Education (2003 : New Delhi, India); Tilak, Jandhyala B. G.; National Institute of Educational Planning and Administration (India) (Delhi : Ravi Books for National Institute of Educational Planning and Administration, 2003)
Contributed papers presented at the National Seminar on Financing of Education at New Delhi in 2003.
Includes statistical tables.
Includes bibliographical references and index.
BIED
Complimentary copy from BIED
Keywords: Education -- India -- Finance; School management and organization -- India; Education -- India -- Finance -- Congresses